Use of Quality Management Tools and Methods Is Essential to Support Effective Governance of Healthcare Organisations - Dinesh Arya (ACHSM, 2020)
For healthcare organisations, a significant governance responsibility is for quality of health care provision. This is an important reason for governance boards to have good understanding of quality management and patient safety systems and processes that guide provision of all aspects of healthcare. It is also important that there is structure to how governance activities are undertaken. Use of quality management tools and methods can provide that structure and support systematic and consistent governance decision making. Using quality management systems and frameworks should be a pre-requisite for effective governance.